(3GdeSGFd GdYTQI aj GdZjHIs - (3GdYcHQj, GdMGQKj, GdHZOGOj, GdcQNj, CHh YHO Gddg, GdTjN GdoepajO, eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe, J (B413s ((3eTgO CejQ GdeDefjf Ydj Hf CHj WGdHs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3aEfj bO NdOJ ef GdcdGe aj hLhH GdEeGeI hGNJUGU eSJMbjgG Ydjge GdSdGe HGdYUeI hJejRge Yf QYGjGge HGdceGd hGdaVd deMGSf GdCaYGd hGdCYdGe (B...s
(3BNQgG (B:s
... (3agPg LedI GdaVhd GdJj VefJ GKHGJ eYGfjgG djJVM dPdc GdMb ajgG djYJHQ Hg Phj GdCdHGH hbO hZjJ HVeGfj aj Pdc hGddg Gdehabs
(3efbhdI Yf fSNI (B: (3GdTjN TjQ eMeO Hf UaQ Ydj GdgePGfj GdLhQbGfj Yf fSNI Yf fSNI Yf fSNI HNW GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\21s
(3GdPQjYI (B16 - 171 ( 957 )s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJhMjO hGdedd hGdfMds